AsiaInfo : returning Chinese startups in the 1990s (A) - Sanderson, Jihong W., (SAGE Knowledge. Cases., 2017)
In 1993 in Texas, a newly formed company, Business Development International (BDI), had no assets, no professional managers, no business plan, and no product. Yet the founders were firm in their resolve to bring information and communication to largely uneducated and isolated China. By 2003, their new venture AsiaInfo was the dominant brand in Chinese Internet Infrastructure and a major force in telecommunications software, and it had grown along with the explosive growth of Internet use in China. As great as the challenge of growing the company to match the rapidly growing industry in China was, other challenges proved even greater.